The Impacts of Global Warming on The Migration Routes of Whales and The Changes - Wang, Yuqing (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper focuses on an in-depth study of the effects of global warming on the migration routes of whales and the changes it brings to marine ecosystems, mainly using humpback whales as an example. The paper discusses how the migration routes of whales, the largest marine mammals that travel long distances between feeding and breeding grounds, have been affected by global warming. The research indicates that while these whales demonstrate remarkable adaptability in adjusting their migration timing, ongoing climate changes may pose significant challenges, particularly in synchronizing their migration with prey availability. The significance of this research lies in the impacts on the entire marine ecosystem, where a decrease in humpback whale populations due to disrupted migration patterns can affect the entire marine food web. In order to mitigate these impacts, related conservation efforts such as protecting whale populations and the ecosystems they support are critical. It is evident that research on subsequent conservation efforts are critical to mitigate these impacts and protect whale populations and the ecosystems they support.